Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Pedagogik Guru - Moh. Zahiq (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
The progress of an institution is greatly influenced by the quality and professionalism of the Madrasa head in leading or empowering the entire madrasah organization, especially madrasa personnel, both educators and education staff. To make all this happen, the Madrasah Principal must have quality leadership in managing all school personnel so that their competence and potential can develop. Leadership of the Madrasah Head as Manager in improving Teacher Pedagogical Competence, namely: Involving teachers in training, Providing freedom for teachers to innovate to improve their skills, Using study time effectively at school, Guiding and providing direction to teachers, Keep up with developments in science and technology. Supporting factors for the leadership of the Madrasah Head as Manager in Increasing Teacher Pedagogical Competence are: Professional madrasa head, High teacher motivation, Adequate Facilities and Infrastructure. and Inhibiting factors for the leadership of the madrasa head as a manager in increasing the pedagogical competence of teachers at namely: a). Mindset (minset), b). A less creative way of teaching